Supply chain digitalization: past, present and future. Issue 2 (17th February 2020) - Seyedghorban, Zahra; Tahernejad, Hossein; Meriton, Royston; Graham, Gary
Abstract: The fourth Industrial Revolution is driving the creation of a more connected ecosystem. Organizations are now re-shaping their strategies to become increasingly transparent, including their supply chain management (SCM). The area of supply chain digitalization is starting to attract growing attention; however, its research status remains unclear. We set out, in this study, to understand what constitutes the underlying structure of its research, what topics have been investigated, what areas need further attention, how the existing literature can be classified and how the discipline can move forward. We applied a mixed-method approach using both quantitative and qualitative techniques to achieve this. A bibliometric analysis of 331 articles with 12, 709 references was first conducted followed by a qualitative content analysis. Results point at a tentative future research agenda featuring five paths: data science-enabled SCM, supply chain agility, humanizing manufacturing through digital manufacturing strategy, Omni-channel and Internet of Things, and resource-based view and beyond.